Reduced contrast sensitivity function is correlated with changes to cone photoreceptors in simple high myopia - Wang, Jiefang; Liu, Xinting; Huang, Jing; Deng, Ruoyun; Zhao, Sijun; Chen, Yulei; Chen, Zhaohe; Wang, Yanli; Rong, Yu; Liu, Qian; Qu, Jia; Mao, Xinjie (Frontiers in Neuroscience, 2024)
Purpose To investigate the contrast sensitivity function (CSF) changes in simple high myopia (SHM) and evaluate the correlations between these changes with the early changes in the retinal microstructure. Methods This prospective study comprised 81 subjects, 20 with emmetropia (EM), 26 with low myopia and moderate myopia (LM/MM), and 35 with SHM. The area under the log CSF curve (AULCSF) and the cut-off spatial frequency (Cut-off SF) were employed as measures of CSF. Adaptive optics (AO) was employed to quantify the cone density, spacing, and regularity. The thickness and blood flow of the retinal sublayers were determined from vertical and horizontal optical coherence tomography angiography (OCTA) A-scans. Swept-source optical coherence tomography (SS-OCT) was employed to analyze the choroidal thickness (CT) and choroidal vascularity using a custom algorithm. Differences in the retinal and choroidal parameters, cone distribution, AULCSF, and Cut-off SF were compared among the three groups. Multivariate linear mixed models were used to elucidate the associations between photoreceptor morphological alterations, retinal and choroidal parameters, and AULCSF. Results The AULCSF and Cut-off SF were significantly lower in the SHM group compared to the EM and LM groups (p < 0.05). The SHM group had less cone density, larger cone spacing, and lower cone regularity than the EM and LM/MM groups (p < 0.05). Moreover, the thickness of the inner segment of photoreceptors (IS), retinal pigment epithelium (RPE) layer and choroid were reduced, and the outer segment of photoreceptors (OS) was thicker in the SHM group compared to the EM and LM/MM groups (all p < 0.05). A longer axial length (AL) was correlated with decreased AULCSF, cone density, and cone spacing (r = −0.800 to 0.752, all p < 0.050). Additionally, decreased CSF was correlated with lower cone density (r = 0.338, p = 0.035). Conclusion Decreased contrast sensitivity was observed in patients with SHM and cone density was significantly correlated with reduced AUCSF.